2022
DOI: 10.1126/sciadv.abl9783
|View full text |Cite
|
Sign up to set email alerts
|

Elongation factor-2 kinase is a critical determinant of the fate and antitumor immunity of CD8 + T cells

Abstract: eEF-2K has important roles in stress responses and cellular metabolism. We report here a previously unappreciated but critical role of eEF-2K in regulating the fate and cytocidal activity of CD8 + T cells. CD8 + T cells from eEF-2K KO mice were more proliferative but had lower survival than their wild-type counterparts after their activation, followed by occurrence of premature senescence and exhaustion. eEF-2K KO CD8 + T cells were more m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…eEF-2 K is another protein with immune-regulatory action identified in the hAMSCs secretome. CD8 lymphocytes from eEF-2 K KO mice show increased proliferation but reduced post-activation survival, likely due to premature induction of senescence via hyperactivation of the Akt-mTOR-S6K pathway [ 53 ]. In addition, several proteins in hAMSCs secretome identified in the Immune cluster have been shown to be crucial for the activation of immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…eEF-2 K is another protein with immune-regulatory action identified in the hAMSCs secretome. CD8 lymphocytes from eEF-2 K KO mice show increased proliferation but reduced post-activation survival, likely due to premature induction of senescence via hyperactivation of the Akt-mTOR-S6K pathway [ 53 ]. In addition, several proteins in hAMSCs secretome identified in the Immune cluster have been shown to be crucial for the activation of immune responses.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Additionally, it has been demonstrated that CD8 + T cells lacking eEF2K exhibit elevated metabolic profiles and are crucial for maintaining the functionality of cytotoxic CD8 + T cells. 19 Defining the role of eEF2K in various cellular processes presents a promising objective for addressing multiple pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, new insights into the biology of eEF2K in inflammatory diseases are needed. While we have recently reported on the role of eEF2K in regulating the fate and antitumor immunity of CD8 + T cells, 19 the full impact of eEF2K on effector T cells, especially CD4 + effector T cells, remains to be fully defined. Given the existing knowledge limitations in these areas, the present study was devised to explore the connection between eEF2K, CD4 + T cells, and inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%